Economy of Mutuality: Merging Financial and Social Sustainability - Jackson, Kevin T. (Journal of business ethics, 2016)
The article posits the concept of economy of mutuality as an intellectual mediation space for shifts in emphasis between market and social structures within economic theory and practice. Economy of mutuality, it is contended, provides an alternative frame of reference to the dichotomy of market economy and social economy, for inquiry about what business is for and what values it presupposes and creates. The article centers around the objective of gaining a broadened understanding of business so as to include not just market economy, but social enterprise and social economy. In pursuit of this objective, a range of various archetypes of business enterprise are considered in light of higher ends of economic life. The highest telos of business encompassing all such archetypes, it is argued, is founded on reciprocity and integral human development. The article concludes that, compared to market economy per se, economy of mutuality provides a better conceptual framework for business in undertaking the challenges of sustainability.